Restrição calórica moderada sobre a adiposidade corporal e o tecido ósseo de ratas sob estado de hipoestrogenismo - Nascimento, Rafael Henrique de Oliveira (Universidade Federal de São Carlos, 2025)
Hypoestrogenism state has been associated with weight gain, obesity and the incidence of osteoporosis. When it comes to weight reduction, calorie restriction (CR) remains the main strategy. However, severe CR (40 to 50%) is associated with damage to bone tissue and favors the incidence of long-term malnutrition. Therefore, the aim of this study was to determine whether 12 weeks of 20% CR is enough to prevent gain in body mass and adiposity without causing additional damage to bone tissue in ovariectomized rats. For this, 40 Wistar rats were randomly divided into 4 groups (n= 10 per group): control (C), control + calorie restriction (C-RC), ovariectomized (OVX) and ovariectomized + calorie restriction (OVX-RC). At 90 days of age, the animals in the OVX and OVX-RC groups underwent bilateral ovariectomy surgery and at 97 days of age the experimental period began, lasting 12 weeks of CR and/or hypoestrogenism. The animals in the C-RC and OVX-RC groups received 20% less feed every day, based on the last week's consumption in the C and OVX groups. The animals' body mass was recorded weekly, and their spontaneous physical activity was recorded every two weeks using a gravimetry apparatus. At 181 days of age, the animals were euthanized and subcutaneous, peritoneal, perigonadal and brown adipose tissue were collected to record absolute and relative mass. The white and red gastrocnemius, gluteus maximus and soleus skeletal muscles and the liver were collected to determine the tissue content of triglycerides (TG). In addition, the right femur was collected to determine biometric, biomechanical, biophysical and biochemical parameters. The data obtained were subjected to analysis of variance up to three ways (time, CR and ovariectomy) and Newman-Keuls post-hoc with a significance level of 5% (p <0.05) and presented as mean±standard deviation. Over the 12 weeks, ovariectomy led to an increase in body mass and food consumption (p <0.001) and in the absolute mass of subcutaneous, peritoneal and perigonadal adipose tissue (p <0.01), while CR led to a significant decrease in all these parameters (p <0.01). With regard to TG content, ovariectomy promoted an increase in the white and red gastrocnemius muscles (p <0.05), gluteus maximus and soleus muscles (p <0.01) and in the liver (p <0.01), while CR reduced it in the muscles (p <0.05), but did not affect the liver (p= 0.15). Ovariectomy led to a decrease in bone volume (p <0.05), bone density and mineral density (p <0.01) and mineral material (p <0.05), while CR did not affect bone volume (p= 0.90) and bone density (p= 0.24), but decreased mineral density and mineral material (p <0.05). Despite this, post-hoc data showed no significant difference in these parameters between the OVX and OVX-RC groups (p >0.05). Overall, 12 weeks of 20% CR was sufficient to reduce body mass and adiposity in animals under hypoestrogenism without leading to additional damage to bone tissue.
Moderate caloric restriction on body adiposity and bone tissue in rats under hypoestrogenism
Keywords: Obesidade; Ratas ovariectomizadas; Gordura visceral; Síndrome metabólica; Osteoporose; Metabolismo energético; Obesity; Ovariectomized rats; Visceral fat; Metabolic syndrome; Osteoporosis; Energy metabolism; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA ENDOCRINA